A STUDY OF THE HISTORICITY OF THE PORTRAYAL OF WOMEN IN VALMIKI RAMAYANA - Singh, Lekhraj; Parveen, Shagufta (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Women have always been the center of human life. Who would not accept the diversity of women, from being a wife who gives pleasure, showing affection as a mother, providing happiness and peace as a sister, making one experience affection as a daughter, serving as a maid. Keeping in mind the human nature, the diversity of women's portrayal in the context of Valmiki Ramayana has been studied and they have been divided into four parts on the basis of their three qualities. Which presented such facts to keep detachment in women. In fact, Valmiki has also shown us two accomplished ascetics, whose spiritual progress was in no way less than that of men.